N-cadherin as a key regulator of collective cell migration in a 3D environment - Shih, Wenting (Landes Bioscience, 2012)
Cell migration is a critical step of normal developmental processes and disease progression. Often, migrating cells interact and maintain contact with neighboring cells. However, the precise roles of cell-cell adhesion in cell migration have thus far been poorly defined. Often in aggressive cancers, N-cadherin is prominently upregulated, yet, these highly motile cells have limited cell-cell adhesion when plated on a stiff 2D substrate. But, the same cells in a 3D matrix migrate as a multicellular cluster. This new observation suggests that N-cadherin-mediated cell-cell adhesion supports cell interactions between migrating cells in a more physiologically relevant 3D matrix, but not on a 2D substrate. While N-cadherin is an integral part of neural synapses, the ectopic expression of N-cadherin in transformed epithelial cells plays an equally important part in initiating pro-migratory signaling, and providing strong yet flexible cell cohesion essential for persistent cell migration in a 3D matrix. The 3D cell migration analysis for studying cell-to-cell interactions exposes the roles of N-cadherin in multicellular migration, and reveals novel insights into cell migration-dependent normal and pathological processes.